Social Media Usage Purposes of Farmers in Selçuklu District of Konya Province - Aysun Yener Ögür; Türkşan Karatekin; Fatma Doğançukuru (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study is to determine the purpose of social media usage of farmers in Selçuklu district of Konya province. The sample volume was determined as 80 according to the stratified random sampling method, with a 95% confidence interval and with a 5% margin of error. Factor analysis was conducted to determine the farmers’ social media usage purposes. Factor analysis was conducted on 19 independent variables and 3 independent variables were identified to determine the reasons for using social media. These variables are called professional development, socialization, and communication. The relationship between professional development, socialization, and communication variables and social media platforms was determined by linear regression analysis. For platforms used for socialization purposes, it was found that Facebook was statistically significant at 1% and Instagram was 5%. According to the regression analysis, platforms used for vocational development purposes, it was found that WhatsApp was statistically significant at 1% and YouTube was 5%. In social media, training, extension, projects, and promotions should be more widely supported in order to support the professional training of enterprises. In addition, pieces of training should be provided for enterprises to use social media platforms more effectively.